ANALISIS DAMPAK PENGGUNAAN PUPUK NPK LODRIN TERHADAP PRODUKSI DAN EFISIENSI USAHATANI KAKAO - Sumarno, Jaka; Anasiru, Rahmat Hanif (Informatika Pertanian, 2018)
Cocoa has been developed in various regions in Indonesia. In developing cocoa farming, farmers still face the problem of low productivity, efficiency and quality of seeds. This is partly due to not using the right fertilizer. This study aims to analyze the effect of NPK Lodrin fertilizer use on the efficiency and income of cocoa farming in Gorontalo. The study was conducted in several Gorontalo cocoa production centers, namely in Gorontalo District and Pohuwato District in 2016. Data collection was conducted by survey method with questionnaires or structured questionnaires for 59 cocoa farmers. Respondents were farmers who used Lodrin NPK fertilizer and farmers who did not use Lodrin NPK fertilizer. The selection of respondents was carried out by stratified random sampling technique. The farming efficiency analysis method uses the Cobb-Douglas stochastic frontier production function model. Financial farming analysis was carried out to determine the level of cocoa farming income with the use of Lodrin NPK fertilizer. The results showed that the use of Lodrin NPK fertilizer significantly affected the increase in production, efficiency and income of cocoa farming in Gorontalo. The average level of farm efficiency both technical, allocative and economic efficiency of cocoa farmers using Lodrin NPK fertilizer is higher when compared to farmers who do not use Lodrin NPK fertilizer. The factors that influence the inefficiency of cocoa farming are farmer education and institutional factors, namely the frequency of counseling, participation in farmer groups, access to credit and technology assistance. The use of Lodrin NPK fertilizer increases the income of cocoa farming, as evidenced by the value of the R / C ratio and the value of return for higher production factors of farmers who use Lodrin NPK fertilizer.